Temozolomide-Induced Changes in Gut Microbial Composition in a Mouse Model of Brain Glioma - Li XC; Wu BS; Jiang Y; Li J; Wang ZF; Ma C; Li YR; Yao J; Jin XQ; Li ZQ (Dove Medical Press, 2021)
Xiao-Chong Li,1,* Bang-Sheng Wu,1,2,* Yi Jiang,1,2 Jie Li,3 Ze-Fen Wang,3 Chao Ma,1 Yi-Rong Li,4 Jie Yao,5 Xiao-Qing Jin,6 Zhi-Qiang Li1 1Department of Neurosurgery, Zhongnan Hospital, Wuhan University, Wuhan, 430071, Hubei, People’s Republic of China; 2Second Clinical School, Wuhan University, Wuhan, 430071, Hubei, People’s Republic of China; 3Department of Physiology, Wuhan University School of Basic Medical Sciences, Wuhan, 430071, People’s Republic of China; 4Department of Clinical Laboratory, Zhongnan Hospital, Wuhan University, Wuhan, 430071, Hubei, People’s Republic of China; 5Department of Biological Repositories, Zhongnan Hospital, Wuhan University, Wuhan, 430071, Hubei, People’s Republic of China; 6Emergency Department, Zhongnan Hospital of Wuhan University, Wuhan, 430071, Hubei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiao-Qing Jin; Zhi-Qiang Li Email redjin@whu.edu.cn; lizhiqiang@whu.edu.cnBackground: Gut microbiota is associated with the progression of brain tumors. However, the alterations in gut microbiota observed during glioma growth and temozolomide (TMZ) therapy remain poorly understood.Methods: C57BL/6 male mice were implanted with GL261 glioma cells. TMZ/sodium carboxymethyl cellulose (SCC) was administered through gavage for five consecutive days (from 8 to 12 days after implantation). Fecal samples were collected before (T0) and on days 7 (T1), 14 (T2), and 28 (T3) after implantation. The gut microbiota was analyzed using 16S ribosomal DNA sequencing followed by absolute and relative quantitation analyses.Results: Nineteen genera were altered during glioma progression with the most dramatic changes in Firmicutes and Bacteroidetes phyla. During glioma growth, Lactobacillus abundance decreased in the early stage (T1) and then gradually increased (T2, T3); Intestinimonas abundance exhibited a persistent increase; Anaerotruncus showed a transient increase (T2) and then a subsequent decrease (T3). Similar longitudinal changes in Intestinimonas and Anaerotruncus abundance were observed in TMZ-treated mice, but the decrease of Anaerotruncus at T3 in the TMZ-treated group was less than that in the vehicle-treated group. No significant change in Lactobacillus was observed after TMZ treatment. Additionally, compared to vehicle control, TMZ treatment led to an enrichment in Akkermansia and Bifidobacterium.Conclusion: Glioma development and progression altered the composition of gut microbiota. Induction of Akkermansia and Bifidobacterium as well as the prevention of the reduction in Anaerotruncus may contribute to the anti-tumor effect of TMZ. This study helps to reveal the association between levels of specific microbial species in the gut and the anti-tumor effect of TMZ.Keywords: glioma, gut microbiota, temozolomide, tumor microenvironment, epigenetics